Redox-Responsive Disulfide Bond-Bridged mPEG-PBLA Prodrug Micelles for Enhanced Paclitaxel Biosafety and Antitumor Efficacy - Chang, Sheng; Wang, Yanfei; Zhang, Tianyi; Pu, Xiaohui; Zong, Lanlan; Zhu, Heyun; Zhao, Luling; Feng, Bo (Frontiers in Oncology, 2019)
The toxicity and side effects of traditional chemotherapeutic drugs are the main causes of chemotherapy failure. To improve the specificity and selectivity of chemotherapeutic drugs for tumor cells, a novel redox-sensitive polymer prodrug, polyethylene glycol-poly (β-benzyl-L-aspartate) (PEG-PBLA)-SS-paclitaxel (PPSP), was designed and synthesized in this study. PPSP was synthesized successfully and PPSP micelle was manufactured via high-speed dispersion stirring and dialysis. The inhibitory effect of PPSP on HepG2、MCF-7 and HL-7702 cell proliferation was investigated with MTT assays. The particle size and zeta potential of this prodrug micelle were 63.77±0.91 nm and -25.8±3.24 mV, respectively. The micelles were uniformly distributed and presented a spherical morphology under a transmission electron microscope. In the tumor physiological environment, the particle size of the PPSP micelles and the release rate of paclitaxel (PTX) were significantly increased compared with those of mPEG-PBLA-CC-PTX (PPCP) micelles, reflecting the excellent redox-sensitive activity of the PPSP micelles. In vitro cell assay demonstrated that PPSP is superior to PTX with respect to the inhibition of two tumor cells and has low toxicity against non-cancerous HL 7702 cells. Moreover, the blank micelle from mPEG-PBLA showed no obvious toxicity to the two tumor cells at different experimental concentrations. In summary, the redox-sensitive PPSP micelle significantly would improve the tumor targeting and anti-tumor activity of PTX and be thus a potential substitute for paclitaxel injection.